Crisis of art knowledge development in Malaysia contemporary visual arts - Mat, Mohamad Faizuan (2013)
In Malaysia, there is a paradox of thinking through the art in the context of visual epistemology. Therefore, this study aims at unlocking the problems in the production of (implicit) knowledge in the art. In addition, Malaysian contemporary artists appear to have insufficient intellectualism values and no shared vision. The lack of scholars in the field of visual arts creates a gap in the visual arts scene in Malaysia. The question of this study was to uncover the main problems in Malaysian visual arts that led to the problem of art knowledge (implicit) development. This is a qualitative study that uses a triangulation method to gather multiple data sources for validation purposes. Furthermore, Face to Face interviews and document studies were conducted to get the respondents' feedback about the problems. The analysis is supported by evidence obtained from observation of the several art discourses. The findings of this study show that art education syllabus and lack of government support is the cause to visual art communication weaknesses. In addition, the findings of this study also present the awareness of valuable contributions in the visual art. It is not merely physical object but also brought the knowledge that can develop further to enhance the communication in the art object.